Between Visibility and Media Performativity. The Role of Interface and Gesturality in Desktop Cinema (Cinéma & Cie. Film and Media Studies Journal, 2021)
This article aims to investigate desktop films as ‘meta-media’ audiovisual forms and to analyse their aesthetics and their meta-reflective potential in the broader framework of contemporary visual and media culture. Screens and interfaces, re-mediated into these films, constitute a second-level media space into the filmic space. They are the only space visually accessible to the spectator, whereby the characters’ gesturality emerges as a form of performing relationship with digital technology, as a posture or a more general engagement with the (media) environment, as an ‘operational trace’ on the screen. Resulting from this visual and narrative structure is the centrality of ‘media performativity’, a concept that will be widely problematized in this article on a theoretical level and analysed as a behavioural pattern that characterizes our daily interaction with the screens surrounding us, as a part of an eco-media system in which action (of the user) and reaction (of the interface) are intervolved and entangled. The concept of media performativity relies on the idea that the individual is no longer separate from the medium throughout the mediation process but is instead deeply and radically involved in the medium itself.
Keywords: Desktop Film; Media Performativity; Interface; Screen Culture; Media Ecosystem